(untitled) (Journal of Information Systems and Technology Management, 2013)
UNATI (Open University of the Third Age), UNESP, Marília campus, has offered subsidies for the development of this work aimed at researching the existing relationships between information mediation processes and technological devices, especially computers, assuming that reading practices and textual construction in on-line environments could help the "third age" population to have access to these devices, thus promoting digital inclusion in this group. Mediation was presented as an interventionist action that, by introducing an intermediate element in the learning process, causes a rupture in the ways of living and personal digital inclusion processes hitherto experienced. In the context of a workshop, we found out that there is a physical relationship between subjects and technological supports and such a contact proved to be necessary, considering that handling a computer required knowledge of procedures, thus furthering a logic of use. It turned out to be necessary to develop actions that would enable the handling of a computer so as to bring about acceptance of these supports. Accordingly, activities were developed so as to articulate reminiscent processes, memories of older adults, the writing down of such memories and the creation of a blog to bring enhanced visibility to the content produced by older people. Such actions have shown that remembering, writing down and posting can reshape not only social relations but somehow significantly promote digital inclusion among older adults.